2018
DOI: 10.4049/jimmunol.1700588
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CD3ζ in NK Cells from Systemic Lupus Erythematosus Patients Confers a Proinflammatory Phenotype

Abstract: Cytotoxic function and cytokine profile of NK cells are compromised in patients with systemic lupus erythematosus (SLE). CD3ζ, an important molecule for NK cell activation, is downregulated in SLE T cells and contributes to their altered function. However, little is known about the role of CD3ζ in SLE NK cells. We studied CD3ζ levels and its contribution to cytotoxic, degranulation, and cytokine production capacity of NK cells from patients with SLE. Furthermore, we studied the human NK cell line, NKL, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Recent studies have investigated the direct cytotoxic action and cytokine profiles of NK cells in the pathogenesis of SLE. For example, the increased cytotoxicity and proinflammatory phenotype of NK cells was shown to be correlated with downregulation of CD3ξ expression in patients with SLE (48); the authors also demonstrated that caspase-3 activity was higher in NK cells from patients with SLE than those from healthy controls and that this contributed to the downregulation of CD3ξ expression in the cells, which enhanced their proinflammatory phenotype.…”
Section: Nk Cells and Autoimmune Diseases Nk Cells And Systemic Autoimentioning
confidence: 93%
“…Recent studies have investigated the direct cytotoxic action and cytokine profiles of NK cells in the pathogenesis of SLE. For example, the increased cytotoxicity and proinflammatory phenotype of NK cells was shown to be correlated with downregulation of CD3ξ expression in patients with SLE (48); the authors also demonstrated that caspase-3 activity was higher in NK cells from patients with SLE than those from healthy controls and that this contributed to the downregulation of CD3ξ expression in the cells, which enhanced their proinflammatory phenotype.…”
Section: Nk Cells and Autoimmune Diseases Nk Cells And Systemic Autoimentioning
confidence: 93%
“…Moreover, Western blot analysis (which detects total protein amount and not just membrane-bound) showed that in patients with low TCR ζ levels, CD3 ε expression was like that of healthy individuals, indicating that its biosynthesis is not affected. Interestingly, previous analysis carried out on NK cells from SLE patients [ 6 ] revealed a diminished expression of CD3 ζ with no effect on other molecules such as NKp30 and NKp46, which also signal via CD3 ζ .…”
Section: Discussionmentioning
confidence: 98%
“…We then went on analyzing caspase-3 activity, involved by some authors in low TCR ζ expression [ 6 , 7 ]. In keeping with previous published data, our results revealed higher enzymatic activity in T cells from patients when compared to control subjects, activity which could be diminished (by 70%) using the Ac-DEVD-FMK inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Treg cells, the number of NK cells was signi cantly decreased in patients with active SLE [26]. However, Suárez-Fueyo et al [27] reported that NK cells in SLE patients exhibited increased cytotoxicity and pro-in ammatory phenotypes that were associated with down-regulation of CD3ζ. These observations are consistent with the present ndings.…”
Section: Discussionmentioning
confidence: 99%